Modeling leaf area at branch level and its vertical distribution in the crown of trees established as dendroenergy crops - Sandoval, Simón; Acuña, Eduardo; Cancino, Jorge; Rubilar, Rafael; Esquivel, Edwin (BOSQUE, 2023)
Studying the crown shapes of trees using modeling techniques is fundamental to understanding the dynamics of crown closure in high- density plantations and can be used as an indicator of intra-specific competition. This study modeled leaf area at branch level and its vertical distribution in the crowns of different aged Acacia melanoxylon, Eucalyptus camaldulensis and Eucalyptus nitens established at 5,000, 7,500 and 10,000 trees ha-1. The effect of planting density and crop age on model parameters was significant in most cases, suggesting the use of branch-level leaf area models adjusted for each condition. The vertical distribution of leaf area was modeled using the Weibull distribution function. The effect of planting density and crop age on the Weibull function parameters was significant. The vertical distribution of foliar area was highly variable at early ages. However, for the species of the Eucalyptus genus it was evident that as the crop grows, the distribution of foliage along the crown tended to be concentrated in the upper part of the trees. On the other hand, higher planting density tended to be correlated with more platykurtic distribution due to the higher level of intraspecific competition.